Hill Edwards, Justene. Savings and Trust: The Rise and Betrayal of the Freedman’s Bank - Chyn, Eric (Journal of Economic Literature, 2025)
Eric Chyn of University of Texas at Austin reviews “Savings and Trust: The Rise and Betrayal of the Freedman's Bank” by Justene Hill Edwards. The Econlit abstract of this book begins: “Chronicles the history of the Freedman's Bank from the perspective of the freed people who invested in the bank as depositors and the experiences of the bank's administrators, detailing how Black depositors' experiences with the bank, and the federal government's unwillingness to hold the perpetrators of its demise accountable, represented an under-explored aspect of the White racial violence that characterized Black people's lives during the Reconstruction and during the Gilded Age.”